A intertextualidade, o gênero lenda e a produção de texto no ensino fundamental - Moura, Josilda Borges (2015)
This academic work shows a discussion about the intertextuality and its importance in the text reading, understanding and producing. It purposes analyze the intertextuality as an expressive resource to build text meanings and to the text producing in the Elementary School, focusing the dialogue between the legend genre and another text genres and, thenceforth, elaborate a pedagogic proposal to be worked in the class. To achieve the proposed objectives, it was necessary to answer the following questions: How the intertextuality can contribute to the reading and writing improvement of the elementary students? How the portuguese teacher can help the elementary students to upgrade their reading and writing skills successfully? Which didactic activities can be applied and which knowledge can be used for this purpose? The search for the answers to these questions took us to a bibliographic research about the subject that has been studying, highlighting some theoretical references, among them, Koch et al. (2012) about intertextuality; Marcuschi (2008) about textual genre; Cascudo (1984) about legend and Schneuwly and Dolz (2004) about didactic sequence, and another authors. Based on these theoretical assumptions, some interpretative analyses were done in some verbal and nonverbal texts, trying to recognize the presence of the intertextuality and how this resource was used by its producers at the creative and sense building process. As a product of these analyses, some reading and text production activities were carefully prepared and organized in a didactic sequence as a pedagogical proposal directed to portuguese teachers in the 6th year of elementary school. Then, it is intended to contribute to improving the quality of education of textual production in the classroom.